Genetic diversity and population structure in Vitis species illustrate phylogeographic patterns in eastern North America. Issue 10 (3rd April 2021) - Péros, Jean‐Pierre; Cousins, Peter; Launay, Amandine; Cubry, Philippe; Walker, Andy; Prado, Emilce; Peressotti, Elisa; Wiedemann‐Merdinoglu, Sabine; Laucou, Valérie; Merdinoglu, Didier; This, Patrice; Boursiquot, Jean‐Michel; et al.
Abstract: Geographical distribution and diversity of current plant species have been strongly shaped by climatic oscillations during the Quaternary. Analysing the resulting divergence among species and differentiation within species is crucial to understand the evolution of taxa like the Vitis genus, which provides very useful genetic resources for grapevine improvement and might reveal original recolonization patterns due to growth habit and dispersal mode. Here, we studied the genetic structure in natural populations of three species from eastern North America: Vitis aestivalis, V. cinerea and V. riparia using different marker types. Vitis aestivalis and V. cinerea showed higher diversity than V. riparia . The two former species are less differentiated, confirming an earlier divergence of V. riparia . V. aestivalis and V. riparia exhibited different genetic groups on both sides of the Appalachian Mountains that could mirror different recolonization routes from southern refugia. Genetic structure was stronger in V. cinerea, for which two varieties (var. berlandieri and var. cinerea ) are morphologically recognized. Our results confirm this distinction and suggest the existence of three other lineages within var. cinerea . These discontinuities appear linked to adaptation of var. berlandieri to dry and limy areas of Texas and partially to the Mississippi River Valley. Rapid range expansions from refugia upon climate warming are also suggested by the low linkage disequilibrium values observed. Furthermore, large variation for downy mildew resistance was observed in the three species. Our findings appeared consistent with the vegetation history of eastern North America.